Enti Inesistenti:: phantasmata in Platone - Botter, Barbara (Revista Archai, 2016)
One of the debated topics about Plato’s Sophist is the distinction between original and image, more precisely, the difference among the original, the true and the false image. It’s only to justify this classification that the philosopher addresses to the demonstration of not”‘being and presents, right from the beginning of the Dialogue, the dualism ‘reality”‘appearance’. The aim of the present paper is creating a relationship between the concepts of not”‘being and appearance, as they are presented in the Sophist, to legitimize the existence of beings that are, although they are not real nor true, the phantasmata. This sort of beings is different from the other kind of image, because they are essentially misleading. Keywords: Imagine (Îµá¼´Î´Ï‰Î»Î¿Î½), apparent image (Ï†á½±Î½Ï„Î±ÏƒÎ¼Î±), untruth, betrayal.